2019
DOI: 10.1097/bor.0000000000000646
|View full text |Cite
|
Sign up to set email alerts
|

Update on lupus epidemiology: advancing health disparities research through the study of minority populations

Abstract: Purpose of reviewThe current review focuses on recent population-based studies that have examined the burden of lupus, disease outcomes, and gaps in quality of care, with an emphasis in research addressing health disparities.Recent findingsThe Centers for Disease Control and Prevention National Lupus Registries underscored higher susceptibility of both systemic lupus erythematosus (SLE) and primary cutaneous lupus among people of color, compared with whites. Not only does SLE disproportionately strike people f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 39 publications
0
47
0
1
Order By: Relevance
“…In the United States, studies have shown that Black patients with SLE, regardless of age at diagnosis, more frequently have kidney involvement, higher disease activity, and higher risk for progression to ESKD. [30][31][32][33][34] Research is still ongoing to determine whether outcome disparities are due to more aggressive disease, genetic disposition, socio-economic causes, systemic racism and unequal access to health care, or a combination of these factors. 30 In this study, kidney function from baseline to the latest follow-up and achievement of remission were assessed as short-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, studies have shown that Black patients with SLE, regardless of age at diagnosis, more frequently have kidney involvement, higher disease activity, and higher risk for progression to ESKD. [30][31][32][33][34] Research is still ongoing to determine whether outcome disparities are due to more aggressive disease, genetic disposition, socio-economic causes, systemic racism and unequal access to health care, or a combination of these factors. 30 In this study, kidney function from baseline to the latest follow-up and achievement of remission were assessed as short-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous estimates of the rates of SLE in the US have been predominantly derived from tertiary care settings and relatively small, homogeneous patient populations, for which limited data are available on key demographic groups in the US (1). Other explanations for the varied estimates, which range from 19 to 241 per 100,000, include racial/ethnic disparities in SLE susceptibility and mortality, differing case definitions, heterogeneous sources for case ascertainment, small populations, possible inaccuracy of self‐report, unreliability in coding in health system databases, and variable access to health care for high‐risk populations (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SLE have a 2.2 to 3.3 times higher relative risk of death than the general population [ 5 ]. The pathogenesis of the disease is still under investigation but revolves around abnormalities in innate and acquired immunity [ 6 ].…”
Section: Discussionmentioning
confidence: 99%